Small airways dysfunction in patients with systemic sclerosis and interstitial lung disease - Panagopoulos, Panagiotis K.; Goules, Andreas V.; Georgakopoulou, Vasiliki E.; Kallianos, Anastasios; Chatzinikita, Eirini; Pezoulas, Vasileios C.; Malagari, Katerina; Fotiadis, Dimitrios I.; Vlachoyiannopoulos, Panayiotis; Vassilakopoulos, Theodoros; Tzioufas, Athanasios G. (Frontiers in Medicine, 2022)
Background: Recent studies report small airways involvement in patients with systemic sclerosis (SSc) while small airways dysfunction is increasingly recognized in patients with interstitial lung disease (ILD) of autoimmune etiology. The objectives of this study were to evaluate small airways function in SSc patients with ILD and explore the effect of treatment by using conventional and contemporary pulmonary function tests (PFTs). Methods: This single-center, prospective, observational study included 35 SSc patients with and without ILD based on HRCT scan. Clinical data were collected from all patients who were also assessed for HRCT findings of small airways disease. Small airways function was assessed by classic spirometry, measurement of diffusing capacity for carbon monoxide, body plethysmography, single breath nitrogen washout (N2SBW) and impulse oscillometry (IOS). The sensitivity of R5-R20, phase III slopeN2SBW and CV/VC methodologies for assessing small airways function was calculated in the total SSc population. Pulmonary function tests were compared between: a) SSc-ILD and non-ILD patients and b) two time points (baseline and follow up visit) in a subset of SSc-ILD patients who received treatment for ILD and were re-evaluated at a follow up visit after 12 months. Results: phase III slopeN2SBW and R5-R20 showed the highest sensitivity for small airways dysfunction among SSc patients. Twenty three SSc patients suffered from ILD and 14 of them had a 12-month follow up visit. SSc-ILD patients exhibited increased phase III slopeN2SBW, increased (R5-R20) difference in IOS, increased airway (Raw) and special airway resistance (sRaw) resistance, and decreased specific airway conductance (sGaw) as compared to SSc patients without ILD, implying impaired small airways function. Radiographic features of SAD on HRCT were observed in 22% of SSc-ILD patients and in none of SSc-non-ILD patients. Comparison of PFTs between baseline and follow-up visit after 12 months in the 14 SSc-ILD patients receiving treatment for ILD, showed improvement of phase III slopeN2SBW, R5-R20 and Raw but no change of sRaw and sGaw. Conclusion: phase III slopeN2SBW and R5-R20 may reveal small airways dysfunction in SSc associated ILD before structural damage and may be partially improved in a subset of patients receiving treatment for ILD.